Implementation of Materiality in Planning Audit of Financial Statements at PT. BPDL in KAP Bambang Sudaryono & Partners - Maidani; Murti Wijayanti (Kusuma Negara Business School, 2021)
Audit Planning and Determination of Materiality is an important component in the implementation of the Audit of Financial Statements. To give a proper opinion that the financial statements are free from the risk of material misstatement, the auditor needs to make a good audit plan and provide a level of materiality in the financial statements. Materiality requires professional judgment with reference to the size or nature of misstatements, which are expected to influence the decisions of users of financial statements. This internship report is to be able to find out how the auditors at KAP BS and Partners determine the audit plan and determine the level of materiality, in the early stages of audit planning. The result of the internship is that the financial statement audit planning is in accordance with audit standard number 300 regarding planning an audit of financial statements, audit standard number 315 regarding the identification and assessment of material misstatements through an understanding of the entity and its environment as well as audit standard number 210 and in accordance with standards audit number 320 which regulates materiality in the planning and implementation stages of the audit.